Studi Pendahuluan Sifat Teknis Tanah Lempung Pada Daerah Rawan Gerakan Tanah Di Dusun Beji Desa Cirahab Kecamatan Lumbir Kabupaten Banyumas - Ary Sismiani; Iwan Rustendi (Techno (Jurnal Fakultas Teknik, Universitas Muhammadiyah Purwokerto), 2021)
In several places in the Banyumas Regency area, land movement problems have often occurred. Several locations have been declared as red zones, one of which is Beji, Cirahab Village, Lumbir District. With such regional conditions, it is necessary to conduct a study of the technical and mechanical properties of the soil in that location including moisture content, density and shear strength parameters related to the possibility of soil movement that will occur. From the results of the test and analysis using 3 specimens, the following data were obtained: water content of 20.22%, 30.36%, 40.31% with a cohesion value of 0.14 kg / cm2, 0.56 kg / cm2, 0.33 kg / cm2, and the internal friction angles of the soil are 30.22 °, 24.47 °, and 18.93 °. While the value of shear stress and displacement at maximum normal stress and moisture content of 20.22%, 30.36%, 40.31% are t(w1) = 0.68 kg / cm2,  t(w2) = 1.01 kg / cm2 ,t (w3) = 0.68 kg / cm2 and dn1 = 15.02%, dn2 = 10.02, dn3 = 13.35%. It can be concluded that the water content always has a very big influence on the value of the soil shear strength parameter. Therefore, the condition of the water content on the soil slope needs to be considered, and it is necessary to carry out further tests and more serious handling at that location.